Impact of integrated behavioral health services on adherence to long-acting injectable antipsychotics - Maister, Ashley J.; McCarthy, Caitlin; Ruszczyk, Lee G.; Evans, Rachael; Maroney, Megan E. (Journal of integrated care (Brighton, England), 2022)
PurposeIntegrated health care occurs when specialty and general care providers work together to address both the physical and mental health needs of their patients. The Substance Abuse and Mental Health Services Administration model of integration is broken into six levels of coordinated, co-located and integrated care. Our institution offers both co-located and integrated care among eight clinic sites. The care team is typically composed of the primary care provider, nurse and medical assistant, but other professionals may be introduced based on the patient’s medical and psychiatric conditions. The purpose of this prospective, quality improvement study was to compare the rates of adherence to long-acting injectable antipsychotics (LAIAs) between both types of integrated primary care settings at our institution. The comparison of the two settings sought to determine which environment provides improved outcomes for patients with serious psychiatric illnesses. Additionally, we aimed to assess the quality of medication-related monitoring and care team composition between care settings, and the ability of pharmacists to deliver interprofessional care team training and education on LAI use in clinical practice.Design/methodology/approachSubjects were identified and included in the study if they had received primary care services from our institution within the previous 12 months. Patient demographic and laboratory variables were collected at baseline and when clinically indicated. The rates of adherence between care settings were assessed at intervals that align with the medication’s administration schedule (e.g. every four weeks). Medication-related monitoring parameters were collected at baseline and when clinically indicated. The interprofessional care team completed Likert scale surveys to evaluate the pharmacist’s LAIA education and training.FindingsThere was not a statistically significant difference detected between integrated primary care settings on the rates of adherence to LAIAs. Additionally, there was not a statistically significant difference between rates of adherence to medication-related monitoring parameters or the effect of the patient treatment team composition. There was a statistically significant difference between pre- and post-session survey scores following interprofessional education and training provided by a pharmacist.Originality/valueBecause overall rates of adherence were low, both primary care settings were found to be equivalent. Our study may have been underpowered to detect a difference in the primary endpoint because of the small sample size. However, our study demonstrates that interprofessional education and training may lend itself to changes in practice, which is evident by the clinically significant relative increase in adherence. The Henry J. Austin Health Center network will be implementing a standard operating procedure regarding LAIA management within the primary care setting. Further studies are needed to assess a larger number of patients between both types of primary care settings, as well as the impact of the clinical psychiatric pharmacist as a member of the treatment team.